OncoLink – advantages of internet and multimedia brought together in order to improve oncological education - Mackiewicz, Małgorzata; Wysocki, Piotr (Contemporary Oncology/Współczesna Onkologia, 1999)
Continuing the series of articles devoted to the – oncology on internet, we present one of the most professional internet homepages referred to as OncoLink, created five years ago by University of Pennsylvania Cancer Center.